Lactiplantibacillus plantarum GUANKE alleviates Zearalenone-induced intestinal dysfunction by modulating oxidative stress and inflammation - Qiaoning Chang; Yanchao Zhao; Han Li; Bin Zhang; Meidi Zhang; Pei Zhao; Jingmin He; Bugao Li; Ming D. Li (PLoS ONE, 2026)
Aims This study evaluated L. plantarum GUANKE’s protective effects on ZEN-induced intestinal dysfunction and explored its molecular mechanisms. Methods In vitro, IPEC-J2 cells were divided into control, ZEN (40 μM), GUANKE (20 MOI), and ZEN+GUANKE groups (24 h treatment). Cell viability (CCK-8), oxidative stress indicators (LDH, ROS, T-SOD, GSH, MDA), and inflammatory cytokine mRNAs ( IL-1β, IL-6, TNF-α, IL-10 ) were detected. In vivo, Balb/c mice were randomized into five groups (control, ZEN, GUANKE, ZEN + LG, ZEN + HG) for 28 days of intervention. Jejunum histology (H&E staining), oxidative stress/inflammatory factors (kits/ELISA), serum intestinal function indices (D-xylose, D-lactate, DAO), and transcriptomic analysis were performed. Results L. plantarum GUANKE significantly improved IPEC-J2 cell viability, reduced LDH release ( P < 0.01) and ROS accumulation (P < 0.001), restored T-SOD/GSH activities (P < 0.05), decreased MDA ( P < 0.05), suppressed pro-inflammatory cytokines (IL-1β, IL-6, TNF-α ; P < 0.05), and upregulated IL-10 ( P < 0.05). In mice , L. plantarum GUANKE increased villus height/crypt depth ratio ( P < 0.01), restored antioxidant status ( P < 0.05), and rebalanced cytokine expression ( P < 0.05 for pro-inflammatory; P < 0.01 for IL-10). Transcriptomic analysis suggested that ZEN activated the NF-κB pathway, while L. plantarum GUANKE treatment was associated with reduced pathway activity.